2021
DOI: 10.1177/0886260520985485
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury as a Mediator of the Associations Between Sexual Harassment and Mental Health Symptoms and Substance Use Among Women Veterans

Abstract: Moral injury is an array of symptoms theorized to develop in response to morally injurious events, defined as events that challenge one’s core moral beliefs and expectations about the self, others, and world. Recent measures of moral injury have distinguished self-directed moral injury (e.g., moral injury symptoms that emerge following the perpetration of morally injurious events) from other-directed moral injury, the symptoms of which are believed to stem from one’s response to actions that others have commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…In that regard, Hamrick, et al. (2022) found that PMIEs of others mediated the association between sexual harassment experience and mental health symptoms among female veterans, This result highlights the importance of PMIEs in understanding psychological difficulties among female veterans in the aftermath of traumatic experiences. Moreover, female veterans seem to be exposed to similar rates of PMIEs and also exhibit similar rates of PTSD, but higher rates of depression and non‐PTSD anxiety disorders compared with male veterans (Freedy et al., 2010).…”
Section: Introductionmentioning
confidence: 94%
“…For example, female combat veterans are more likely to be exposed to traumas of an interpersonal nature, such as child abuse or sexual assault (for review, see Zinzow et al, 2007), and that female veterans report greater life stressors and work stress compared to males (Lehavot et al, 2018;Vogt et al, 2011). In that regard, Hamrick, et al (2022) found that PMIEs of others mediated the association between sexual harassment experience and mental health symptoms among female veterans, This result highlights the importance of PMIEs in understanding psychological difficulties among female veterans in the aftermath of traumatic experiences. Moreover, female veterans seem to be exposed to similar rates of PMIEs and also exhibit similar rates of PTSD, but higher rates of depression and non-PTSD anxiety disorders compared with male veterans (Freedy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research data support the possibility that exposure to transgressive acts may be related to higher rates of depressive disorders. This exposure may also facilitate destructive behaviors, such as substance and alcohol abuse (Hamrick et al, 2021), self-handicapping behaviors and demoralization (e.g., Zerach & Levi-Belz, 2019), and even suicidal ideation and behavior (Levi-Belz, Dichter, et al, 2020; Williamson et al, 2020). Moreover, to date, most studies have explored the link between exposure to PMIEs and PTSD (e.g., Barnes et al, 2019; Levi-Belz, Greene, et al, 2020).…”
Section: The Present Studymentioning
confidence: 99%